Fabrication of Biomimetic Hybrid Liposomes via Microfluidic Technology: Homotypic Targeting and Antitumor Efficacy Studies in Glioma Cells - Arduino I; Di Fonte R; Sommonte F; Lopedota AA; Porcelli L; Li J; Serrati S; Bártolo R; Santos HA; Iacobazzi RM; Azzariti A; Denora N (International Journal of Nanomedicine)
Ilaria Arduino,1 Roberta Di Fonte,2 Federica Sommonte,2 Angela Assunta Lopedota,1 Letizia Porcelli,2 Jiachen Li,3 Simona Serrati,2 Raquel Bártolo,3 Hélder A Santos,3 Rosa Maria Iacobazzi,1 Amalia Azzariti,2,* Nunzio Denora1,* 1Department of Pharmacy–Pharmaceutical Sciences, University of Bari, Bari, 70125, Italy; 2IRCCS Istituto Tumori “Giovanni Paolo II”, Bari, 70124, Italy; 3Department of Biomaterials and Biomedical Technology, University Medical Center Groningen (UMCG), The Personalized Medicine Research Institute (PRECISION), University of Groningen, Groningen, AV, 9713, Netherlands*These authors contributed equally to this workCorrespondence: Rosa Maria Iacobazzi, Department of Pharmacy–Pharmaceutical Sciences, University of Bari, Bari, 70125, Italy, Tel +39 0805442808, Email rosa.iacobazzi@uniba.itIntroduction: The treatment of glioblastoma is hindered by the blood–brain barrier (BBB) and rapid drug clearance by the immune system. To address these challenges, we propose a novel drug delivery system using liposomes modified with cell membrane fragments. These modified liposomes can evade the immune system, cross the BBB, and accumulate in tumor tissue through homotypic targeting, thereby delivering drugs like paclitaxel and carboplatin more effectively.Methods: In this work, the hybrid liposomes were synthesized using microfluidics and integrating 3D printing to produce the microfluidic devices. In vitro, we explored the homotypic targeting capability, BBB passing ability, and therapeutic efficacy of paclitaxel and carboplatin.Results: The production of hybrid liposomes by microfluidics has been key to creating high-quality biomimetic nanoparticles, and the integration of 3D printing has simplified the production of microfluidic devices, making the process more efficient and economical. In vitro experiments have shown that these drug-loaded biomimetic hybrid liposomes are able to reach the homotypic target, cross the BBB, and maintain the efficacy of paclitaxel and carboplatin.Conclusions: The development of biomimetic hybrid liposomes represents a promising approach for the treatment of glioblastoma. By combining the advantages of liposomal drug delivery with the stealth properties and targeting capabilities of cell membrane fragments, these nanoparticles can potentially overcome the challenges associated with traditional therapies. Keywords: bioinspired materials, biomimetic nanoparticles, glioblastoma cells, emerging technology, drug delivery system, microfluidics